Morphological and taxonomic assessment of the Olearia furfuracea complex (Celmisiinae, Astereae, Asteraceae) - Nicol, Duncan A.; Saldivia, Patricio (Phytotaxa, 2025)
The subtribe Celmisiinae (Asteraceae) is an Australasian clade of ca. 160 species across six genera. Recent morphological and molecular analyses found several well-supported clades within the subtribe. One of those clades is the “Olearia furfuracea complex”, a group of five currently recognised species endemic to the North Island of New Zealand. Although they are morphologically distinct from the rest of the subtribe, the discrimination between the five species is not so clear. This study analysed the morphological circumscription of the five species with respect to each other with the aim of testing the species boundaries. Olearia allomii and O. pachyphylla were found to be distinct from each other and the other three. Olearia furfuracea, O. thomsonii, and O. townsonii were found to grade into one another through a range of quantitative, qualitative, and morphometric analyses. Morphometric and morphological evidence supports the recognition of three species and suggests retaining only O. allomii, O. pachyphylla, and O. furfuracea. Additionally, recent studies suggest a new classification, in which Olearia species belonging to Celmisiinae should be shifted into Shawia. Accordingly, two new combinations are made: Shawia allomii (Kirk) Nicol & Saldivia comb. nov., and Shawia pachyphylla (Cheeseman) Nicol & Saldivia comb. nov. The name Shawia furfuracea is reinstated. Five heterotypic synonyms are proposed, and typification is fully revisited. Morphological descriptions, maps and illustrations are also provided.